The development of statistical lettering by the teaching books and the National Curricular Common Base - Santos, Wagner Dias (2018)
This article explains how the approach developed by textbooks, in relation to the contents of Statistics and Probability, provides students with the development of Statistical Literacy. Six collections were analyzed - three of the final years of elementary school and three of high school, approved by the National Program of Didactic Book (PNLD) - with more distribution in the country, according to information obtained on the website of the National Fund for Education Development (FNDE). The praxeological organization of Yves Chevallard (1999) was used as a methodology for the analysis of the questions in the textbooks. The levels of graphical comprehension, tabular and Statistical Literature were established and, finally, it was indicated how the transnumeração in the works occurs, according to our theoretical reference. The results show that the analyzed collections do not allow a full development of Statistical Literacy. In addition, some characteristics that the works have to meet are highlighted so that they can be adapted to the proposals of the National Curricular Common Base (BNCC).